Neutrophil Methods and Protocols - Quinn, Mark T.; Quinn, Mark T.; DeLeo, Frank R.; DeLeo, Frank R. (Methods in Molecular Biology, 2014)
Neutrophils, the most abundant white cells in humans, serve as the primary cellular defense against infection. Neutrophil Methods and Protocols, Second Edition provides a concise set of protocols written by leading researchers in the field for assessing basic neutrophil functions, investigating specialized areas in neutrophil research, and completing step diagnostic assays of common neutrophil disorders. Topics covered include an overview of neutrophils and their role in host defense and inflammation; methods most commonly used for isolating neutrophils from humans and other animal species; procedures for subcellular fractionation of human neutrophils, analysis of in vivo transmigrated neutrophils, generation of mature neutrophils from induced pluripotent stem cells, and analysis of neutrophil gene expression; methods for investigating priming, oxidant production, phagocytosis, bactericidal activity, and extracellular trap formation; and protocols for investigating neutrophil adhesion, chemotaxis, and outside-in signaling via integrins. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Neutrophil Methods and Protocols, Second Edition is a comprehensive source for detailed explanations and applications of the most modern methodological advances in neutrophil biology. Both basic scientists and clinicians will find a collection of this caliber to be an invaluable aid in their work with neutrophils.